Pengaruh Model Learning Cycle 5E Berbasis Eksperimen Terhadap Kemampuan Berpikir Kritis Fisika Peserta Didik Kelas XI SMAN 1 Gerung - I'in Senja Septiana; Ahmad Harjono; Hikmawati Hikmawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
This research aims to determine the effect of experimental based learning cycle 5E model to the critical thinking ability of physics students class XI SMAN 1 Gerung. This research is a quasi experimental research with design called "untreated control group design with pretest and posttes". The population in this study is all students of class XI SMA Negeri 1 Gerung, and sampling technique using purposive sampling. There are two samples taken are class XI MIPA-3 as experiment class and XI MIPA-2 as control class. The data collection critical thinking ability using the technique to description of 6 questions. Based on the result, it is found that the average posttest of experimental critical thinking ability is 70,28 and control class is 62,39. The obtained data were first tested for normality and homogeneity. Both classes were normally distributed and homogeneous, followed by hypothesis testing using statistical test (t-test polled variance). The hypothetical test of critical thinking ability was obtained by ÃÂ of 3.38, of 1.99 at significant level of 0.05, because ÃÂ  is greater than ÃÂ , H0 is rejected and Ha is accepted. The conclusion of this research, there is influence of experimental based learning cycle 5E model to the critical thinking ability of physics learners class XI SMAN 1 Gerung.